Hubungan Karakteristik Demografi dengan Tingkat Pengetahuan dan Perilaku Masyarakat Dusun Wohan Tampingan Kabupaten Magelang Terhadap Covid19 - Febriana Astuti; Jarot Styapurnomo (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT It has been more than two years since the Covid-19 pandemic, and it is not sure when this pandemic will end. The community has to start adapting to these conditions by continuing to do physical activities safely, applying health protocols in a disciplined and optimal manner, and not giving up fighting the Covid-19 pandemic. To prevent Covid-19, the community’s knowledge and behavior are very influential.Therefore this quantitative research focuses on examining the relationship between knowledge, demographics, and people's behavior related to Covid-19. This quantitative analytic study uses purposive sampling to determine the study's participants and uses a cross-sectional approach. There were 160 participants in this study. Data analysis used univariate and bivariate, which were processed using the Chi-Square test to see the correlation. The data of this study were analyzed using univariate and bivariate analysis, which was processed using the Chi-Square test to see the correlation between demographic characteristics, knowledge, and behavior, as well as the Spearman correlation test to see the relationship between knowledge and behavior.The results of the univariate analysis showed that the highest level of knowledge was in the "good category (86.9%), and the highest level of behavior was in the "good category (69.4%). The results of the bivariate analysis showed that there was no correlation between gender and knowledge (p-value 0.078), there was no correlation between age and knowledge (p-value 0.198), and there was no correlation between education and knowledge (p-value 0.223). In the face of behavior, it was found that there was no correlation between gender and behavior (p-value 0.456), there was no significant correlation between age and behavior (p-value 0.165 ), and there was no significant correlation between education and behavior (p-value 0.223). Age, sex, and educational demographic factors have no relation on knowledge or behavior. The Wuhan Tampingan hamlet community in the Magelang Regency behaves in a manner that is significantly correlated with its amount of understanding about Covid-19.Keywords : Demographic, knowledge, behavior, COVID-19  ABSTRAKPandemi Covid-19 sudah dua tahun lebih melanda dan diperkirakan belum diketahui kapan akan berakhir. Masyarakat sudah harus mulai beradaptasi dengan kondisi tersebut dengan cara tetap beraktivitas fisik dengan aman menerapka protokol kesehatan secara disiplin dan optimal serta tidak menyerah melawan pandemi covid-19. Pengetahuan dan perilaku masyarakat terhadap Covid-19 sangat penting agar pencegahan terhadap covid-19 dapat dilakukan. Penelitian ini bertujuan untuk mengetahui hubungan karakteristik demografi dengan pengetahuan dan perilaku dusun Wohan Tampingan Kabupaten Magelang tentang Covid-19. Desain penelitia nadalah kuantitatif analitik dengan pendekatan Cross Sectional.Teknik pengambilan sampel menggunakan purposive sampling, sampel yang digunakan 160 responden. Analisis data menggunakan univariat dan bivariat yang diolah menggunakan uji Chi Square untuk melihat hubungan karakteristik demografi dengan pengetahuan dan perilaku serta uji uji korelasi spearman untuk melihat hubungan pengetahuan dan perilaku.Hasilanalisis univariat didapatkan bahwa tingkat pengetahuan terbanyak kategori baik (86,9%), dan perilaku terbanyak kategori baik (69,4%). Hasil analisis bivariat didapatkan bahwa tidak terdapat hubungan antara jenis kelamin dengan pengetahuan (p value 0,078), tidak terdapat hubungan antara usia dengan pengetahuan (p value 0,198), dan terdapat tidak terdapat hubungan Pendidikan dengan pengetahuan (p value 0,223). Apabila ditinjau dari perilaku didapatkan bahwa tidak ada hubungan antara jenis kelamin dengan perilaku (p value 0,456), tidak terdapat hubungan yang signifikan antara usia dengan perilaku (p value 0,165 ), tidak terdapat hubungan yang signifikan antara pendidikan dengan perilaku (p value 0,223). Karakteristik demografi usia, jenis kelamindan pendidikan tidak berhubungan dengan pengetahuan dan perilaku. Kesimpulan dari penrlitian ini adalah terdapat hubungan yang signifikan antara tingkat pengetahuan dengan perilaku masyarakat dusun Wohan Tampingan Kabupaten Magelang tentang Covid-19.Kata kunci: Demografi, pengetahuan, perilaku, COVID-19